IMPLEMENTASI UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG HAK TENAGA KERJA WANITA DI ALFAMART DAN INDOMARET DI KOTA PEKANBARU - Gita Prina; Zahirman Zahirman; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack : this research background in the background by the large number of problems Still associated with employment in the city of Pekanbaru in particular labor women. The visible phenomena related to the employment problem of these women, among other things: the amount of labour women are increasing each year, there are still large number of women employed in the evening, still the number of rights the rights of these women's labor not given such rights to breastfeed the baby, menstrual leave, etc. So the author would like to see how the employment rights of women, and alfamart indomaret in pekanbaru. This descriptive qualitative research methods. The used instrument that is now composed of 15 questions about the law regarding the rights of female labor. The data were analyzed using the formula P = f/Nx100% to find out the percentage of answers from the respondents. The calculation of the percentage of overall respondents answer obtained answers "no" as much as 70% is in the range of 0%-50% and the percentage of "Yes" answers as much as 30% are in the range of 51%-100% for the implementation of law No. 13 year 2003 about the labor rights of women. Based on the results of the study it can be concluded that the implementation of the law No. 13 Year 2003 regarding labor rights of women have not been carried out properly, should companies or labor party women are encouraged to better understand and dig regarding Act No. 13 year 2003 that especially on the rights of the workforce are women.Keywords : implementation, law number 13 year 2003, women's Labor